Pengalaman Perawat dalam Penggunaan Rekam Medis Elektronik di Rumah Sakit Panti Rini Yogyakarta - Ernest Novema Dhamar; Margareta Hesti Rahayu (I Care Jurnal Keperawatan STIKes Panti Rapih, 2020)
Background: Nursing documentation through electronic medical records is expected to provide convenience for nurses. Purpose: explore nurses' experiences in using electronic medical records. Method: this study was a qualitative research, used purposive sampling technique. The research was conducted at Panti Rini Hospital Yogyakarta and conducted in May 2020 and interviewed 5 nurses and 1 head of the ward in the inpatient ward. Result: this study found 4 themes: 1) the use of electronic medical records to provide convenience, 2) supporting factors for the use of electronic medical partners, 3) obstacles in the use of electronic medical records 4) the expectations of nurses in using electronic medical records. Conclusion: the hospital needs to improve facilities and infrastructure so that the available system is able to accommodate the need for electronic nursing care documentation.